INFLUENCE OF POST-BLEACHING TIME INTERVALS USING 37% CARBAMIDE PEROXIDE ON DENTAL SUBSTRATE ADHESION - Yamakami, Shelyn Akari; Faraoni, Juliana Jendiroba; Caslini, Daniela Pires; Chinelatti, Michelle Alexandra; Palma-Dibb, Regina Guenka (Iniciação Científica Cesumar, 2017)
The aim of this study was to evaluate the influence of post-bleaching time intervals using 37% carbamide peroxide on dental substrate adhesion. Fifty bovine incisors were sectioned in two groups of 4X4 mm standard blocks to obtain 50 specimens in each group (n=50). In fifty blocks, the dentin (D) was analyzed and in the other 50 the enamel (E). Blocks were subjected to bleaching treatment and restored with Single Bond/z250 according to post-bleaching time intervals (0, 7, 14 and 21 days). Twenty-four hours after adhesive/resin cylinders on substrate confection, shear bond strength test (SBS) was performed in an universal test machine. Means in MPa and their respective standard deviations were: E – control: 31.89 (2.39); T0: 19.07 (2.00); T7: 24.97 (4.89); T14: 29.71 (4.89); T21: 40.91 (4.75) and D – control: 18.90 (3.64); T0: 2.22 (0.41); T7: 3.79 (0.75); T14: 5.95 (0.79); T21: 8.40 (0.87). Data were submitted to ANOVA and Tukey (p< 0.05) tests. The bond strength value for the enamel was statistically higher than the dentin, and both were lower than the control group that had similar results after 21 days post-bleaching. In dentin group, the control showed superior bond strength and was statistically different in relation to other times. It was concluded that bleaching had negative influence on adhesion. Therefore it is necessary to wait, at least, 21 days after bleaching to restore the enamel.